Teknologi Sebagai Kegiatan Manusia Dalam Era Modern Kehidupan Masyarakat - Faisal Tamimi; Siti Munawaroh (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
This research examines Technology as a Human Activity in the Modern Era of Community Life, technology is something that we cannot avoid in the current era of modernization, all human activities using technology have progressed very rapidly. By using this sophisticated technology, humans in the modern era can make it easier to do work. At first technology developed gradually along with the progress of culture and civilization. Because technology is a rapidly advancing cultural development, humans develop technology more quickly. Because technology provides structure for human activity, it can be said that technology does not simply assist human activity, but also reshapes it, creating new activities that define the self, community, and good. Moral-ethical decisions, social relationships, space, time, perception, and self-concept. Transformation through technological advances For example, when complex new instruments or techniques are used in medical practice, it not only changes what doctors do but also how people think about health, disease, and medical care. Social and moral life is influenced by the technological devices we appraise. They enhance human worldviews, social practices, organizations, values, and lifestyles. Nowadays, it is difficult to be truly active in making technological decisions while technological devices are most often imposed on us, forcing many things on us. Apart from having a positive impact, the development of this technology also has a negative impact which can hinder direct interaction between people, where people already have a lot of indirect interaction, everyone is already dependent on technology, especially smartphones and social media, all activities already involves social media, be it news, business, learning and others.